« Going limp » : Usages et mises en scène de la vulnérabilité comme stratégie militante lors d’actions désobéissantes aux États-Unis - Charlotte Thomas Hébert (Genre, Sexualité et Société, 2021)
This article focuses on physical non-cooperation - aka “going limp” - during civil disobedience arrests in the United States. It contends that by performing refusal, activists deploy their vulnerability as a strategic tool. Going limp allows us to rethink and go beyond the labels that define resistance as “active” and “passive” and tend to obscure how complex action repertoires are, especially when used by so-called minorities. These labels also tend to erase agency and portray civil disobedience as a moral and selfless act, which contributes to depoliticizing the practice. Resisting arrest by going limp disrupts the separation between the public and private spheres, demonstrating that bodies do not have equal access and claim to public space and that bodily and emotional experience shape activist commitment.